Effect of Fe Supplement on The Physical Fitness of Girls at School (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Physical fitness protects the body from viruses (Santoso 2021) post-covid-19. In Yogyakarta, 63.17% of students have "Not Good" physical fitness, and 51.61% of are Girls. Physical activity is related to physical fitness (Alamsyah, Hestiningsih et al. 2017), a lack of iron intake also causes low physical fitness (Sitoayu, Yuslaili et al. 2020). In 2018, only 35.1% of girls received iron tablets in Bengkulu Province (NINGSIH 2020). Does the low achievement of iron tablets cause low physical fitness? Objective; Knowing the Effect of Fe Supplements and Physical Activity on Physical Fitness. The method used in writing this journal is a Literature Review of 18 research journals from 2000 to 2023 obtained from the Google Scholar and Pubmed search engines. Conclusion; There are 4 (four) main factors that have been proven significant several times and were re-examined by this new researcher, these factors include; 1. Physical activity, 2. Hemoglobin levels, 3. Iron intake, and Anemia. the relationship between iron supplementation and physical fitness of female adolescents at school has not been proven.